Chart Review Study of Subjects Administered Amnionic Membrane for Treatment of Joint Pain - Timmons, Ruben Berrocal; Fearnot, Neal E; Leckrone, Michael E (Current trends in biotechnology and pharmacy, 2018)
Treatment of joint pain with injection of amnionic membrane has not been adequately studied. Determine if patients who received cryopreserved particulate amnionic membrane (CPAM) injected into painful back and knee joints experience less back or knee pain, improve physical ability, and use less opiates and NSAIDs over a 12 week time period. Charts were reviewed for 20 consenting patients receiving CPAM, clinically available from tissue banks, injected into joints to relieve pain consistent with the clinical practice at a single center. Ten subjects had back pain, and 10 subjects had knee pain. VAS pain scores improved from 7.5 to 1.1 over 12 weeks (p<0.001). WOMAC daily activity function score improved from 46 to 11over 12 weeks (p<0.001). Opiate usage decreased from 55% to 15% over 12 weeks (p<0.001). NSAID usage decreased from 80% to 10% over 12 weeks (p<0.001). Location of injection was not a significant covariate factor for any outcome. Thus, amnionic membrane injection into painful back and knee joints improves pain and physical function, and decreases opiate and NSAID usage for at least 12 weeks.